Tahap kepuasan kerja dan komitmen organisasi dalam kalangan guru kolej vokasional: pendekatan structural equation model - Affendi, Fatimah (2014)
This study intended to ascertain the impact of job satisfaction of Kolej Vokasional teachers on their commitment towards organization. Besides that, it also investigated specifically factors contributing to job satisfaction, namely promotional opportunities, leadership, working environment, workload, and relationship with colleagues, and management style. The study used self-administered questionnaires which were distributed to 308 teachers from Kolej Vokasional Batu Pahat, Kolej Vokasional Kluang, Kolej Vokasional Muar, Kolej Vokasional Perdagangan Johor Bahru and Kolej Vokasional ERT Azizah, Johor Bahru, Johor.. Data was analyzed using SPSS 16 for descriptive analysis while AMOS 18 was used for Structural Equation Modeling (SEM). The study found that promotional opportunities, workload and relationship with colleagues significantly affect job satisfaction of teachers. Most importantly, this study also confirmed that there is a significant relationship between job satisfaction and work commitment. Overall, the findings of this study indicate that satisfied teachers will be committed to their job, and promotional opportunities, workload and relationship with colleagues should be given due consideration as they significantly affect job satisfaction level among teachers.